Empowering School Students Through Simple Digital Marketing Portfolio Creation - Winahyu, Pawestri; soraya, Zalkha; Satoto, Eko Budi; Adelia, Sherry; Sarifuddin (PT Inovasi Pratama Internasional, 2025)
This community service programme employed a participatory, experiential learning approach to equip secondary school students at Sangkhom Islam Wittaya School, Hat Yai, Thailand, with basic digital marketing skills through the creation of digital portfolios. Thirty students, supported by three teachers, took part in interactive lectures, demonstrations, guided practice, project-based learning, and feedback sessions. Quantitative results from paired sample t-tests showed a significant improvement in knowledge and skills, with mean scores increasing from 55.40 (SD = 8.25) in the pre-test to 78.30 (SD = 7.10) in the post-test (t(29) = 11.25, p < 0.05). Qualitative findings reinforced these outcomes: students demonstrated active participation and creativity, reported greater confidence in applying digital concepts, and produced coherent portfolios; teachers also confirmed improvements in digital competencies aligned with the school’s literacy objectives. Overall, the programme proved effective in delivering practical and relevant learning experiences that significantly enhanced students’ digital literacy and entrepreneurial potential in line with the demands of the digital era.